2021
DOI: 10.1038/s41398-021-01728-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and metabolome in a non-human primate model of chronic excessive alcohol drinking

Abstract: A relationship between the gut microbiome and alcohol use disorder has been suggested. Excessive alcohol use produces changes in the fecal microbiome and metabolome in both rodents and humans. Yet, these changes can be observed only in a subgroup of the studied populations, and reversal does not always occur after abstinence. We aimed to analyze fecal microbial composition and function in a translationally relevant baboon model of chronic heavy drinking that also meets binge criteria (drinking too much, too fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The 16S rRNA sequencing results showed that the β -diversity of LC, YEL, and YEH was significantly higher than that of the AL group ( Supplementary Figures S1D,E ), with no significant difference among the three groups. Studies indicated that ethanol can significantly decrease the level of β-diversity, which is closely related to alterations in the gut microbiota ( Piacentino et al, 2021 ; Xia et al, 2021 ). In terms of gut microbiota composition, the ratio of Firmicutes to Bacteroidetes in the YE group was lower than that in the alcohol-induced model group ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA sequencing results showed that the β -diversity of LC, YEL, and YEH was significantly higher than that of the AL group ( Supplementary Figures S1D,E ), with no significant difference among the three groups. Studies indicated that ethanol can significantly decrease the level of β-diversity, which is closely related to alterations in the gut microbiota ( Piacentino et al, 2021 ; Xia et al, 2021 ). In terms of gut microbiota composition, the ratio of Firmicutes to Bacteroidetes in the YE group was lower than that in the alcohol-induced model group ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome consists of trillions of bacteria which have a critical role in host’s health ( Huang et al., 2020 ; Khan et al., 2020 ; Abdullaeva et al., 2021 ; Piacentino et al., 2021 ). Firmicutes and Bacteroidetes are the two dominant bacterial phyla in human gut ( Guan et al., 2021 ; Kameli et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…predictions [141]. However, it must be noted that ITS prediction accuracy is much lower than 16s prediction accuracy [101].…”
Section: Discussionmentioning
confidence: 89%